Association between C-reactive protein and chronic pain in US adults: A nationwide cross-sectional study. - Chunsheng Huang; Qizhen Tong; Qiaoling Tong (PLoS ONE)
Background Chronic pain has emerged as a significant global public health concern. Hence, it is imperative to acquire a more comprehensive comprehension of these characteristics in the adult population of the United States in order to facilitate the development of effective interventions. The objective of this study is to ascertain the prevalence of chronic pain among people in the United States and investigate its association with C-reactive protein (CRP) levels. Methods The present study employed a cross-sectional design and utilized data from three cycles of the National Health and Nutrition Examination Survey (NHANES). The study aimed to investigate the relationship between chronic pain status, CRP levels, and potential confounding factors. The study incorporated individuals who successfully fulfilled chronic questionnaires and had CRP assays. Weighted univariate and multivariate logistic regression analyses were performed to examine the correlation between chronic pain and CRP levels. To explore the non-linear relationship, weighted restricted cubic spline (RCS) with three knots coupled with a weighted logistic regression model to assess the dose-response relationship between CRP (continuous variables) and chronic pain. Results A total of 10,680 (Weighted 250,814,660.8) adult participants with complete information were included in the analysis and 2612 (Weighted 67978784.88, 27.1%) subjects met the definition of chronic pain. Compared with participants without chronic pain, those with chronic pain had a higher CRP level (P < 0.001). The results of the multivariable adjusted logistic regression model suggested that the highest CRP quartile (CRP >  0.52 mg/dL) was associated with a 32% increase in the risk of chronic pain compared with the lowest CRP quartile (CRP ≤  0.09 mg/dL). The RCS result showed that the OR of chronic pain and CRP displayed a linear relationship (P = 0.027, Non-linear P = 0.541). Conclusions The study found a significant correlation between CRP levels and the presence of chronic pain among people in the United States. Individuals exhibiting elevated levels of CRP demonstrated a heightened propensity for experiencing chronic pain in comparison to individuals with lower CRP levels. Additional investigation is necessary to explore the presence of a causal association between the two variables, as well as the potential underlying mechanisms.